MONITORING ARUS DAN TEGANGAN PENERANGAN LAMPU JALAN BERBASIS INTERNET OF THINGS - Hidayah, Arini Alfa; Amperawan (Teknik Elektro Polsri, 2025)
The purpose of this research is to develop an Internet of Things (IoT) based system capable of monitoring the current and voltage of street lighting. This system utilizes the INA219 sensor to measure the voltage and current generated by the solar panel, which is then sent in real-time through the NodeMCU module using WiFi to the Blynk application. Test results show that the INA219 sensor has good accuracy, with an average error of 0.73% for voltage and 0.75% for current. This monitoring system enables effective remote monitoring of solar cell performance, with data displayed on the Blynk app in real-time and accurately.